Analisis Faktor Daya Tarik Dakwah Ustazah Halimah Alaydrus Di Youtube - Mila Thahira Siregar; Hasan Basri M. Nur; Fakhruddin (Kalam: Jurnal Agama dan Sosial Humaniora, 2026)
The development of digital technology has changed the pattern of da'wah from face-to-face to online media-based, including da'wah models without showing the preacher's face. This research is motivated by the dominance of visual aspects in digital da'wah, especially on the YouTube platform, amidst the phenomenon of da'wah that does not display the physical representation of the communicator. This study aims to analyze the attractiveness of Ustazah Halimah Alaydrus' da'wah delivered without facial visuals, and to understand how the message remains effective and attractive to the audience. The method used is a descriptive qualitative approach with data collection techniques through video content analysis based on the categories of faith, morals, and worship, as well as in-depth interviews with purposively selected audiences. Data analysis uses an interactive model that includes data reduction, data presentation, and drawing conclusions. The results show that the appeal of da'wah does not depend on the visual aspect, but rather on the credibility of the communicator which includes expertise, trustworthiness, and non-physical attractiveness. Soft delivery, the use of simple language, and appropriate voice intonation can create deep emotional and spiritual engagement. Audiences also demonstrated positive responses, including increased understanding, emotional engagement, and positive changes in attitudes. Thus, preaching without physical representation has proven effective as an alternative communication model in the digital age.